DSP mutations and arrhythmogenic cardiomyopathy. (1st May 2019) - Maruthappu, T.; Posafalvi, A.; Castelletti, S.; Delaney, P.J.; Syrris, P.; O'Toole, E.A.; Green, K.J.; Elliott, P.M.; Lambiase, P.D.; Tinker, A.; McKenna, W.J.; Kelsell, D.P.
Summary: Arrhythmogenic Cardiomyopathy (AC) is a relatively rare inherited disorder of the heart muscle and can lead to sudden death in patients, often under 35 years of age. AC can be very difficult for doctors to diagnose because the initial symptoms are often subtle so they can go unnoticed. In a rare form of AC, affected patients also have striking curly hair and abnormally thickened skin on the palms and soles. This can make the diagnosis easier to make. This study, from London, UK, looked at families with a more common form of AC caused by mutations in desmoplakin, a protein which acts as a "glue" between cells in both the heart and skin. We show that the majority of family members with AC had curly hair, and a significant proportion of these patients also had the condition causing thickening of the skin. Skin biopsies from patients with AC revealed abnormalities in several proteins responsible for connecting cells to one another, these proteins are also critical in the heart for conducting impulses throughout the heart muscle and signalling contraction. Early diagnosis and family screening are the key goals in the management of AC. This study has identified two novel features in AC caused by desmoplakin mutation, the first is the presence of curly hair and the skin condition in the majority of affected family members. The second is the identification of abnormalities in several proteins in skin biopsies taken from patients with AC. Examination of the skin and hair could therefore provide a unique window of opportunity to facilitate the prompt diagnosis of AC.